The Unstable Trochanteric Fractures Treated with Proximal Femoral Nail Antirotationversus Sliding Hip Screw - Sangkomkamhang, MD, Thananit (Journal of Southeast Asian Orthopaedics, 2022)
Purpose: To compared the complications and functional outcomes of patients with unstable trochanteric fractures AO/OTA 31-A2 treated with a proximal femoral nail antirotation (PFNA) device versus sliding hip screw (SHS). Methods: A prospective randomized study of patients with unstable trochanteric fractures AO/OTA 31-A2 from January 2010 to December 2012 was performed. A total of 181 patients were randomized into two groups: the PFNA group (n = 95) and the SHS group (n = 86). Perioperative and postoperative data, functional outcomes, and complications were recorded and assessed. Results: Although the reoperation rate was lower in the PFNA group than in the SHS group, there was no significant difference between the reoperation rates of the two groups in the patients with unstable trochanteric fractures. There was also no significant difference in functional outcome between the PFNA group and the SHS group. The SHS group had a prolonged operative time and produced more blood loss than the PFNA group. Conclusion: For treatment of unstable trochanteric fractures (AO/OTA 31-A2) of proximal femur, the sliding hip screw should remain the standard treatment of care. However, the PFNA device is still useful for the treatment of unstable trochanteric fractures (AO/OTA 31-A2) that involve the lateral cortex.